Online Teaching and Teachers’ Mental Burdens during the COVID-19 Pandemic - Syahputri, Veni Nella; Idami, Zahratul; Ismail, Nyak Mutia (Universitas Serambi Mekkah, 2020)
This study focused on outlining the psychological effects on teachers caused by the implementation of online teaching and learning during the COVID 19 pandemic. A descriptive qualitative approach was employed in conducting this study. There were 34 female teachers aged between 25-38 years old involved as respondents. The instrument used was a questionnaire sent through WhatsApp application. The data were analyzed using interactive analysis (data condensation, data display, and data verification). The results show that 34 respondents (100%) experienced uncertainty to their students; 58.8% (20 respondents) have physical pain and fatigue; 41.2% (14 respondents) experienced demotivation; 38.2% (13 respondents) tend to procrastinate their work; 67.7% (23 respondents) have bad time management; and 94.3% (32 respondents) experienced the feeling of isolation. Hence, it is suggested that educational institutions provide a care unit to handle any potential problems on teachers’ mental health. Keywords: mental burdens, online teaching, psychological health, psychological effects, and COVID-19 pandemic.